METHODS AND ADVANTAGES OF EARLY CLOSING. - Heckert, J. Brooks (The Accounting Review, 1929)
There is no longer any considerable discussion on the point that the accountant must prepare condensed summary statements of the operations for the year and the resulting financial condition, and must maintain current records of the assets, liabilities and proprietorship items. But the function of greatest value to the organization is to provide analytical information which will promote operating efficiency, regardless of the complexity of operating details, organization or responsibility. Certain of these analyses to be of value must be compiled and used daily, weekly or monthly and must exhibit transactions immediately following their performance, and these statements must so interlock with the general program as to preclude duplication of work and result in the final formal closing at an early date each period. Few controllers in any of these fields of business activity could justify their outlay for clerical and statistical force, except on the ground of promotion of operating efficiency. To accomplish this task the accountant must analyze results and the cost of securing these results in such manner as to determine the desirability of existing policies and the performance of individuals in carrying out these policies.